2014
DOI: 10.1016/j.bbagrm.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Sfmbt2 10th intron-hosted miR-466(a/e)-3p are important epigenetic regulators of Nfat5 signaling, osmoregulation and urine concentration in mice

Abstract: Sfmbt2-hosted miR-466a-3p and its close relatives are often among the most significantly up-regulated or down-regulated miRNAs in responses to numerous deleterious environmental stimuli. The exact roles of these miRNAs in cellular stress responses, however, are not clear. Here we showed that many Sfmbt2-hosted miRNAs were highly hypertonic stress responsive in vitro and in vivo. In renal medulla, water deprivation induced alterations in the expression of miR-466(a/b/c/e/p)-3p in a pattern similar to that of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…6 A – D ). As a matter of fact, these two miR families have been reported to similarly respond to detrimental cellular stress and share comment target genes, for example, Nfat5 in immune cells and Dcx and Patah1b1 in neural stem cells (57,58). Our study delineated an important regulatory mechanism of miR-466 and miR-200 against the diabetic environment, in which the UPR transducer IRE1α functions as the upstream regulator and the proangiogenic factor ANGPT1 acts as an effector.…”
Section: Discussionmentioning
confidence: 99%
“…6 A – D ). As a matter of fact, these two miR families have been reported to similarly respond to detrimental cellular stress and share comment target genes, for example, Nfat5 in immune cells and Dcx and Patah1b1 in neural stem cells (57,58). Our study delineated an important regulatory mechanism of miR-466 and miR-200 against the diabetic environment, in which the UPR transducer IRE1α functions as the upstream regulator and the proangiogenic factor ANGPT1 acts as an effector.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, another member, mmu‐miR‐669c was shown to be associated with the regulation of glutathione metabolism in the liver of aging mice [62]. Recent report also showed that mmu‐miR‐466(a/e)‐3p were important epigenetic regulators of renal Nfat5 signaling, osmoregulation and urine concentration in mice [63]. Therefore, this is the first report showing the function of miR‐466 of the gene family – miR‐467 in human.…”
Section: Resultsmentioning
confidence: 94%
“…Nevertheless, this cluster has been studied in mice and shown to play a role in osmoregulation in the kidney. 82 Another miR-466 isoform (not part of this cluster), miR-466g was also shown to target SGK1. 83 As miRs-466a/e & b/c were upregulated after a 24-hours aldosterone stimulation, our focus shifted to the miR-466 F I G U R E 6 Heatmap of % of miRs predicted to bind to the mRNAs listed (from miRDB predictions).…”
Section: Discussionmentioning
confidence: 99%